Pengaruh Reputasi, E-Service Quality, dan E-Trust Terhadap Kepuasan Nasabah Generasi Z Pengguna Call Center Bank Syariah Indonesia (BSI) - Saepullah, Putra Rizqy Dwi; Waluyo, Bambang (Lembaga Penelitian dan Pengembangan Masyarakat IAINU Kebumen, 2025)
The development of digital services in the Islamic banking sector demands optimal service quality, particularly for Generation Z customers who are digital natives. This study aims to analyze the influence of reputation, e-service quality, and e-trust on the satisfaction of Generation Z customers using the Call Center services of Bank Syariah Indonesia. A quantitative approach was employed using regression analysis with SmartPLS 4.0. Data were collected through a questionnaire distributed to 200 randomly selected respondents. The results indicate that reputation and e-service quality have a significant influence on customer satisfaction, while e-trust does not show a significant effect. These findings highlight the importance of building a strong corporate image and improving responsive and reliable digital services to enhance customer satisfaction. Bank Syariah Indonesia is advised to optimize its call center performance, particularly in terms of response speed, information reliability, and meeting the expectations of Generation Z. This research offers theoretical contributions to the Islamic banking literature and practical recommendations for digital service strategy development.